2022
DOI: 10.1186/s12885-022-10410-z
|View full text |Cite
|
Sign up to set email alerts
|

Finding My Way-Advanced: can a web-based psychosocial intervention improve the mental quality of life for women with metastatic breast cancer vs attention-control? Study protocol of a randomised controlled trial

Abstract: Background Women living with metastatic breast cancer (MBC) are at risk of significantly impaired quality of life (QOL), symptom burden, distress and fear of progression, and unmet needs, yet they face barriers to accessing evidence-based psychosocial treatments. Our group therefore developed Finding My Way-Advanced (FMW-A), a web-based self-guided psychosocial program for women with MBC. This study aims to assess its efficacy in improving mental and other QOL domains, distress, fear of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A recent review demonstrated that people with early-stage diagnosis, who are more likely to receive treatment with curative intent, may benefit from psychosocial interventions focused on increasing positive affect and building psychological resources (Salsman et al, 2019). Reduction of distress in curatively treated people can also lower health service utilization (Beatty et al, 2022). Interventions aimed at reducing distress currently focus on targeting moderators such as emotional and social functioning (Beatty et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review demonstrated that people with early-stage diagnosis, who are more likely to receive treatment with curative intent, may benefit from psychosocial interventions focused on increasing positive affect and building psychological resources (Salsman et al, 2019). Reduction of distress in curatively treated people can also lower health service utilization (Beatty et al, 2022). Interventions aimed at reducing distress currently focus on targeting moderators such as emotional and social functioning (Beatty et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of distress in curatively treated people can also lower health service utilization (Beatty et al, 2022). Interventions aimed at reducing distress currently focus on targeting moderators such as emotional and social functioning (Beatty et al, 2022). An assets-based approach to after-care which focuses on exploring existing resources rather than assessing potential deficits in cognitive functioning may offer a wider scope for intervention.…”
Section: Implications For Cancer Carementioning
confidence: 99%
“…This is a self-guided psychosocial program that is web-based. Beatty et al [ 48 ], published a study protocol to test its efficacy in improving the quality of life of women with metastatic BC. The protocol compares two telehealth interventions FMW-A and the Australian BC Network’s online application “My Journey”, which is a minimal intervention attention control.…”
Section: Telemedicine and Bc Beyond Covid-19mentioning
confidence: 99%
“…The protocol compares two telehealth interventions FMW-A and the Australian BC Network’s online application “My Journey”, which is a minimal intervention attention control. The hypothesis is that FMW-A can reduce health system burden while mitigating symptoms and enhancing the quality of life of patients with breast metastatic disease [ 48 ]. Examples of on-going trials on telemedicine in BC management after the pandemic are mentioned in Table 2 .…”
Section: Telemedicine and Bc Beyond Covid-19mentioning
confidence: 99%